The Relationship between Corruption and Economic Development - Ndongo, Thadde (International Journal of Humanity and Social Sciences, 2024)
Purpose: The general objective of the study was to explore the relationship between corruption and economic development. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to corruption and economic development. Preliminary empirical review revealed that corruption significantly impedes sustainable economic growth by undermining investor confidence, distorting market mechanisms, and perpetuating cycles of poverty and inequality. Strong institutional frameworks, democratic governance structures, and targeted policy interventions were identified as crucial in mitigating corruption risks and fostering economic development. The findings underscored the importance of transparency, accountability, and international cooperation in combating corruption and promoting inclusive growth, highlighting the need for evidence-based strategies to address corruption challenges and advance human well-being globally. Unique Contribution to Theory, Practice and Policy: The Institutional theory, Political Economy theory and Public Choice theory may be used to anchor future studies on corruption and economic development. The study offered valuable recommendations with significant contributions to theory, practice, and policy. Theoretical insights enriched our understanding of corruption's causal mechanisms, while practical recommendations guided practitioners in addressing corruption risks and promoting ethical behavior. Policy recommendations urged governments to prioritize anti-corruption reforms and enhance international cooperation. These contributions bridged the gap between theory and practice, empowering stakeholders to combat corruption effectively and foster sustainable economic development.